Manajemen risiko bank syariah di era digital: Strategi mitigasi pada pembiayaan bank syariah - Affandy, Faza Ainunnisa (Maliki Interdisciplinary Journal, 2024)
This article discusses risk management of Islamic banks in the digital era with a focus on risk mitigation strategies in Islamic bank financing. Initially, the definition of banking and the role of banks in society was explained. Next, the challenges for Islamic banks in developing digital banking are explained, especially the unpleasant customer experience with sharia banking products. Banking risks are identified, especially financing risks which can come from internal or external sources of the bank. To control risk, Islamic banks must carry out risk management by identifying, measuring, monitoring and controlling various risks. Before providing financing, sharia banks conduct a customer feasibility analysis based on the 3 pillar philosophy and 5C analysis. Financing risk mitigation is discussed through risk identification, customer business evaluation, installment capabilities, and supervision during the financing process. In conclusion, to face the challenges of the digital era, Islamic banks need to increase risk management efforts and mitigate financing risks.